Validation of Prostate Imaging Reporting and Data System Version 2 Using an MRI-Ultrasound Fusion Biopsy in Prostate Cancer Diagnosis - Kim, See Hyung; Choi, Mi Sun; Kim, Mi Jung; Kim, Young Hwan; Cho, Seung Hyun (American journal of roentgenology (1976), 2017)
The purpose of our study was to prospectively assess Prostate Imaging Reporting and Data System (PI-RADS) version 2 using an MRI-ultrasound fusion biopsy. This study included 295 consecutive patients with 478 lesions who underwent multiparametric MRI and subsequent MRI-ultrasound fusion biopsy between December 2014 and September 2016. Lesions were assessed by using an overall score of PI-RADS version 2. One radiologist assessed the presence or absence of clinically significant prostate cancer in the whole gland and in subgroups of the peripheral zone and transition zone by using cutoff values of ≥ 4 and ≥ 3. Histologic examination of MRI-ultrasound fusion biopsy specimens was used as the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated to assess the utility of PI-RADS version 2 for the diagnosis of clinically significant prostate cancer. The overall PI-RADS version 2 scores showed an accuracy of 82.2% (393/478) for the whole gland, with a cutoff value of ≥ 4 granting sensitivity of 90.0% (90/100), specificity of 80.1% (303/378), PPV of 83.3% (90/108), and NPV of 81.8% (303/370). The overall scores showed accuracies of 84.7% (301/355) in the peripheral zone and 74.7% (92/123) in the transition zone. When we applied an arbitrary overall score of ≥ 3, accuracy was 68.6% (328/478), sensitivity was 94.6% (124/131), specificity was 58.7% (204/347), PPV was 51.6% (124/240), and NPV was 85.7% (204/238). PI-RADS version 2 has an overall good performance for the diagnosis of clinically significant prostate cancer.